ANALISIS STABILITAS DAN KONSISTENSI CAMPURAN ASPAL SLURRY SEAL DENGAN PENAMBAHAN ABU AMPAS TEBU - Suciati, Herlina; Arba'in, Akhmad Khildan; Panusunan, Panusunan; Room, Akhbar Ilmiah (SIGMA TEKNIKA, 2024)
Road maintenance through the addition of surface layer thickness is costly because it involves the use of various and large amounts of materials, labor, and tools. The use of slurry seals can improve pavement uniformity by reducing roughness and grooves, covering the pavement surface, and repairing roughness without the need for resurfacing. In this research, bagasse ash was used as a filler in the slurry seal mixture, and several tests were carried out including consistency test, setting time test, and Marshall Test. The addition of bagasse ash by 25% to 100% in the slurry seal mixture shows an influence on the decreasing consistency value, due to the characteristics of bagasse ash which tends to absorb water. In addition, the setting time becomes faster due to the increased workability of the mixture and the bonding reaction between cationic emulsion asphalt with cement filler and bagasse ash which accelerates the bonding process. The Marshall test results showed an increase in stability value caused by the silica (SiO₂) content in bagasse ash. Meanwhile, the flow value decreased due to the larger volume of bagasse ash granules, which filled the gaps between aggregates and made the mixture denser with lower deformation.